The influence of candidates' physical attributes on patient ratings in simulated assessments of clinical practice. (2nd November 2022) - Brown, C. A.; Badger, K.; Reid, M. D.; Westacott, R.; Gurnell, M.; Reed, M. W. R.; Chamberlain, G.; Hatfield, E.; Sharif, A.; Sam, A. H.
Abstract: Background: We have previously shown that clinical examiners' scoring is not negatively impacted when a candidate has a tattoo, unnatural hair colour, or a regional accent. We investigated whether these physical attributes in exam candidates impact patient scoring. Methods: Simulated/real patients were randomly assigned to watch five videos of simulated candidate performances of a cranial nerve examination: clear fail, borderline, good, 'clear pass' without an attribute, and 'clear pass' with one of the attributes (tattoo, purple hair, accent). Participants scored domains of communication and professionalism. We compared scores for the clear pass candidates with and without attributes. Results: One hundred and eighty three patients participated. The total scores for the candidates with tattoos and purple hair were higher than the candidate with no physical attribute ( p  < 0.001). For the candidate with a Liverpool English accent no difference was identified ( p  = 0.120). Conclusions: The presence of certain physical attributes (tattoos or purple hair) was associated with higher scores given by patients to candidates in a simulated physical examination station.